PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVC SD NEGERI 032 KUALU - Mislian '; Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was conducted because of the result of learning social study class IVC SD Negeri 032 Kualu. From 35 students who achieve KKM just 15 students (42.86%) while students who did’nt complete 20 students (57.14%) with an average of 67.43. The purpose of this research to improve learning outcomes IPS class IVC SD Negeri 032 Kualu with the application of learning models talk think write. The results obtained by the average value of 67.43 basic score increased in the first cycle of 13.39% to 76.46. In the second cycle the average value of students also increased by 26.78% to 85.49. On the basis of completeness score IPS student learning outcomes is only 42.86% (not finished). After the professor of applied learning model Think Talk Write (TTW) in the first cycle classical completeness increased to 74.29% (not finished), the second cycle of classical completeness obtained are increased to increase to 100%. Activities of teachers at the first meeting of 71.43% with both categories. The second meeting increased to 75% in both categories. In the second cycle increased to 85.71% with the category very well. At a meeting of the second meeting of the second cycle, the activities of teachers increased to 92.86% with the category very well. Activities of students in the first cycle of the first meeting activity students acquire a percentage of 67.86% in both categories. The second meeting of the first cycle to 75% in both categories. At the first meeting of the second cycle of student activity increased to 82.14% with the category very well, and at the second meeting of the second cycle increased again to 89.29% with the category very well.Keywords : Numbered Heads Together, learning outcomes IPS